The impact of maternal obesity on in vivo uterine contractile activity during parturition in the rat. Issue 5 (2nd March 2023) - Muir, Ronan; Khan, Raheela; Shmygol, Anatoly; Quenby, Siobhan; Elmes, Matthew
Abstract: Maternal obesity is associated with increased risk of prolonged and dysfunctional labor and emergency caesarean section. To elucidate the mechanisms behind the associated uterine dystocia, a translational animal model is required. Our previous work identified that exposure to a high‐fat, high‐cholesterol (HFHC) diet to induce obesity down‐regulates uterine contractile associated protein expression and causes asynchronous contractions ex vivo. This study aims to investigate the impact of maternal obesity on uterine contractile function in vivo using intrauterine telemetry surgery. Virgin female Wistar rats were fed either a control (CON, n  = 6) or HFHC ( n  = 6) diet for 6 weeks prior to conception, and throughout pregnancy. On Day 9 of gestation, a pressure‐sensitive catheter was surgically implanted aseptically within the gravid uterus. Following 5 days recovery, intrauterine pressure (IUP) was recorded continuously until delivery of the 5th pup (Day 22). HFHC induced obesity led to a significant 1.5‐fold increase in IUP ( p  = 0.026) and fivefold increase in frequency of contractions ( p  = 0.013) relative to CON. Determination of the time of labor onset identified that HFHC rats IUP ( p  = 0.046) increased significantly 8 h prior to 5th pup delivery, which contrasts to CON with no significant increase. Myometrial contractile frequency in HFHC rats significantly increased 12 h prior to delivery of the 5th pup ( p  = 0.023) compared to only 3 h in CON, providing evidence that labor in HFHC rats was prolonged by 9 h. In conclusion, we have established a translational rat model that will allow us to unravel the mechanism behind uterine dystocia associated with maternal obesity. Abstract : This is the first study to investigate the effect of dietary induced adiposity upon uterine contractile activity in vivo. Uterine contractile activity was measured by surgically implanting a pressure sensitive telemeter probe into the gravid uterus using aseptic techniques. Using this surgical technique, it was identified that feeding a high‐fat, high‐cholesterol diet to induce adiposity significantly prolonged labor compared to lean control fed animals.